Meta‐analysis of clinical trials examining the benefit of structured home exercise in patients with peripheral artery disease. Issue 4 (21st February 2019) - Golledge, J.; Singh, T. P.; Alahakoon, C.; Pinchbeck, J.; Yip, L.; Moxon, J. V.; Morris, D. R.
Abstract : Background: Supervised exercise is recommended for the management of peripheral artery disease (PAD); however, the uptake is limited. Structured home exercise programmes may be more feasible, but their effectiveness is unclear. This systematic review and meta‐analysis examined the benefit of structured home exercise programmes for treating PAD in comparison to controls not receiving an exercise programme. Methods: A literature search was conducted to identify RCTs comparing structured home exercise with controls not receiving an exercise programme among patients with PAD. To be included, studies had to report outcomes from treadmill or corridor walking tests, or objective assessment of physical activity. Inverse variance‐weighted meta‐analysis was performed to compare changes in maximum walking distance and intermittent claudication onset distance in treadmill tests, walking distance during a 6‐min walking test, and physical activity measured using a pedometer or accelerometer. Summarized results are presented in terms of standard deviation differences. Results: Eleven randomized trials involving 807 patients were included. Follow‐up ranged from 2 to 24 months; only one trial included follow‐up beyond 12 months. Meta‐analyses showed that structured home exercise programmes led to significant improvements in maximum walking distance (mean difference (MD) 0·32, 95 per cent c.i. 0·15 to 0·50; P < 0·001), intermittent claudication onset distance (MD 0·45, 0·27 to 0·62; P < 0·001), walking distance in a 6‐min walking test (MD 0·28, 0·09 to 0·47; P = 0·004) and physical activity (MD 0·27, 0·11 to 0·43; P = 0·001). Conclusion: This meta‐analysis suggests that structured home exercise programmes are effective at improving walking performance and physical activity in the short term for patients with PAD. Abstract : Supe rvised exercise is an established treatment for peripheral artery disease. This meta‐analysis suggests that structured home exercise programmes can also be effective in improving walking performance and increasing physical activity in patients with peripheral artery disease. Small to moderate improvement